2003
DOI: 10.1016/s0266-7681(03)00172-4
|View full text |Cite
|
Sign up to set email alerts
|

Trigger Thumb: Results of a Prospective Randomised Study of Percutaneous Release with Steroid Injection Versus Steroid Injection Alone

Abstract: One hundred and twenty-seven trigger thumbs in 115 adult patients were randomised to either percutaneous release with steroid injection (n=66) or steroid injection alone (n=61). Two patients, one from each group, were lost to follow-up. Percutaneous release with steroid injection produced satisfactory results in 91% of cases whereas steroid injection alone produced satisfactory results in 47% of cases. One case in the percutaneous group developed stiffness and one in the injection group developed cellulitis. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
87
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(93 citation statements)
references
References 20 publications
2
87
0
Order By: Relevance
“…Similarly high success rate were recorded by Freiberg et al 93% [6], Cecen et al 83% [18] and Clark et al 83% [24]. Other studies have demonstrated lower success rates (Shakeel et al 70% [19], Kolind-Sorensenb 67% [3], DalaAli et al 66% [21], Murphy et al 64% [13], Rhoades et al 63% [25], Taras et al 62% [23], Lambert et al 60% [12], Maneerit et al 47% [14]). Sato et al [26] found the trigger cure rate of 57% with single injection and 86% after two injections.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Similarly high success rate were recorded by Freiberg et al 93% [6], Cecen et al 83% [18] and Clark et al 83% [24]. Other studies have demonstrated lower success rates (Shakeel et al 70% [19], Kolind-Sorensenb 67% [3], DalaAli et al 66% [21], Murphy et al 64% [13], Rhoades et al 63% [25], Taras et al 62% [23], Lambert et al 60% [12], Maneerit et al 47% [14]). Sato et al [26] found the trigger cure rate of 57% with single injection and 86% after two injections.…”
Section: Discussionmentioning
confidence: 61%
“…[10]. In various studies, a single injection of corticosteroid relieved symptoms in 47-87% of patients with trigger finger [6,11,12,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…However, clinicians may not describe this phenomenon quantitatively, so the literature generally presents the effectiveness of intervention using simple and convenient physical examinations, as well as patients' self-reported satisfaction questionnaires. 1,6,[7][8][9][10][11][12][13][14] Kinematics investigations may provide a new approach for quantifying the inappropriate movements of the trigger digit. For example, clinical experience is usually based on a four-or five-grade taxonomy.…”
Section: Discussionmentioning
confidence: 99%
“…In prior studies, researchers usually used simple physical examinations, such as clinical observations of range of motion (ROM) or movement abnormality and pain rating and selfreported satisfaction questionnaires to evaluate conditions before and after treatment. 1,[6][7][8][9][10][11][12][13][14] With these methods, clinicians can easily and conveniently assess treatment outcomes; however, little research has focused on objectively assessing the efficacy of surgical release based on quantifiable measures. To describe hand movements thoroughly, uses of three-dimensional and dynamic goniometric measures to represent thumb and finger ROM based on computer-aided motion analysis techniques were recently reported.…”
mentioning
confidence: 99%
“…Trigger finger is a common condition with a reported prevalence of 2% to 20% [1,2]. Generally, trigger finger affects women more than men and the age distribution is bimodal with one group below six years of age and the other in their fifth and sixth decade of lif.…”
Section: Introductionmentioning
confidence: 99%